If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 26 = 8x + -11 Reorder the terms: 26 + 12x = 8x + -11 Reorder the terms: 26 + 12x = -11 + 8x Solving 26 + 12x = -11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 26 + 12x + -8x = -11 + 8x + -8x Combine like terms: 12x + -8x = 4x 26 + 4x = -11 + 8x + -8x Combine like terms: 8x + -8x = 0 26 + 4x = -11 + 0 26 + 4x = -11 Add '-26' to each side of the equation. 26 + -26 + 4x = -11 + -26 Combine like terms: 26 + -26 = 0 0 + 4x = -11 + -26 4x = -11 + -26 Combine like terms: -11 + -26 = -37 4x = -37 Divide each side by '4'. x = -9.25 Simplifying x = -9.25
| 0.0003X-2.3245Y=X+Y-3.2543 | | -11+2n+2-6=-8-5n | | -X+20Y=20 | | 10x+7y=1446 | | 8p^2-14pq+5q^2=0 | | 10x-7y=1446 | | 9x=-21 | | 5(2x-4)=10x+20 | | 0.7x+2=16 | | 3x^2-7x-6=x | | -8-n=3*(2n-4) | | -3(2x-1)-2x=3+x | | x^2-2.45+1.50=0 | | 4r+13=7r+1 | | 8x+4x-40=100-8x | | y^2+4-10y-20+9=0 | | 3x-1=3x-9 | | 0.25t+8=5 | | 84=3(-4+8n) | | 8-u+10u=8u-2 | | -32+p=43 | | 0.35t+8=5 | | 5+3n=3n+5 | | q(q-6)=0 | | -6x+3-2X=3+x | | -6x+3-2X=3(x) | | 2x-22=-48 | | -288=8(-6m+6)-8m | | 10logx=100 | | (2x+7)=4 | | n+(-18)=-42 | | -32+x=10-2x |